1999
DOI: 10.1039/a906182g
|View full text |Cite
|
Sign up to set email alerts
|

New quadrupolar fluorophores with high two-photon excited fluorescence

Abstract: New quadrupolar fluorophores that exhibit enhanced twophoton excited fluorescence were designed according to a molecular engineering approach based on push-push and pull-pull elongated molecules built from a rigid conjugated core (either dihydrophenanthrene or dithienothiophene).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 174 publications
(118 citation statements)
references
References 17 publications
3
109
1
Order By: Relevance
“…(1(1)-1'(4))+(1 (1) [117] four lowest excited states of π conjugated systems were theoretically investigated using using the ab initio response theory. The materials were synthesized and characterized by Kim et al [123] and Ventelon et al [122] Agren et al showed that their theoretical findings were consistent with the correlation between large 2PA crosssections and a π center. Although 1PA spectra were strongly correlated to the molecular length, this was not always the case for 2PA in the visible domain [117].…”
Section: ∆E Evmentioning
confidence: 68%
See 1 more Smart Citation
“…(1(1)-1'(4))+(1 (1) [117] four lowest excited states of π conjugated systems were theoretically investigated using using the ab initio response theory. The materials were synthesized and characterized by Kim et al [123] and Ventelon et al [122] Agren et al showed that their theoretical findings were consistent with the correlation between large 2PA crosssections and a π center. Although 1PA spectra were strongly correlated to the molecular length, this was not always the case for 2PA in the visible domain [117].…”
Section: ∆E Evmentioning
confidence: 68%
“…A types with the aim of increasing 2PA absorption cross-sections [118][119][120][121][122][123]. However, the choice of functional groups and linkages, the most appropriate for developing chromophores with large 2PA characteristics, is still under active investigation [124][125][126][127][128][129][130][131][132][133][134][135].…”
Section: D-π-a D-π-d or A-π-a Molecular Structures Have Been Propmentioning
confidence: 99%
“…In the quest of improving NLO properties, attention has been essentially focused on dipolar molecules for several decades. [1][2][3] More recently, quadrupolar systems have been designed and investigated [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and have shown improved properties, in particular with respect to the trade-off between optical transparency and NLO performance. Lately, attention has turned toward multipolar [22][23][24][25][26][27][28][29][30][31][32][33] and branched structures including dendrimers.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the donor-acceptor configuration of 2PA active chromophores, it was also established by Bredas et al that increasing the length and charge transfer of the molecules results in an increase in 2PA crossections and may also result in a significant shift of 2PA to longer wavelengths [6]. Complementarily, Agren et al theoretically studied four lowest excited states of π conjugated systems experimentally produced and characterized by Kim et al [10] and Ventelon et al [9] using ab initio response theory. They showed that their theoretical findings were consistent with the correlation between large 2PA crossections and a π center, but that though the one photon absorption (1PA) spectra was strongly correlated to the molecular length this was not always the case for 2PA in the visible domain [5].…”
Section: D-π-a D-π-d Ormentioning
confidence: 99%
“…In recent studies fluorene derivatives have been extended to D-π-π-A and A-π-π-A types with the aim of increasing 2PA absorption cross-sections [6][7][8][9][10]. However, the choice of functional groups and linkages the most appropriate for developing chromophores with the largest 2PA characteristics it is still under active investigation.…”
Section: D-π-a D-π-d Ormentioning
confidence: 99%